The alteration of extracellular signal-regulated kinase (ERK) activity of COS7 cells from interphase to mitosis - Shi, H.; Shen, L. (Cellular and Molecular Biology, 2010)
Although many reports have suggested that ERK1/2 activity is increased in interphase and inhibited in mitosis, the change of ERK1/2 activity from interphase to mitosis is largely undefined. In this study, we examined the alteration of ERK1/2 activity in COS7 cells in response to nocodazole. Nocodazole-treated or nocodazole-untreated COS7 cells were stimulated by EGF. We found that ERK1/2 activity of nocodazole-treated cells was decreased with prolonged time of cells treated with nocodazole while being increased in nocodazole-untreated cells. COS7 cells became round after being treated with nocodazole for 4 hr. And from the time point, ERK1/2 activity was gradually and significantly inhibited. Furthermore, we showed that MEK activity was greatly decreased compared with nocodazole-untreated cells after the cells were treated by nocodazole for 8 hr and then EGF. In addition, the migration of cells was inhibited in response to nocodazole. Taken together, we concluded that ERK1/2 activity was gradually inhibited from interphase to mitosis and the cell migration was affected by nocodazole.